The COVID-19 experience among international migrant workers in the Republic of Korea: knowledge and awareness of treatment and immigration policies - Jayoung Park; Jongho Heo; Woong-Han Kim; Sugy Choi (BMC Public Health)
Abstract Introduction The COVID-19 pandemic has exposed various health risks and inequities experienced by international migrant workers. The number of migrant workers in the Republic of Korea (ROK) is rapidly growing and is expected to continue growing. Health related research on migrant workers in ROK is limited, especially among undocumented migrant workers who were more vulnerable to the pandemic. This study aims to examine the experiences of migrant workers and their knowledge and awareness of treatment and immigration policies during the pandemic. Methods We used data from the International Migrant Workers’ COVID-19 Health Literacy and Access to Medical Care project, a cross-sectional survey conducted with international migrant workers residing in ROK in 2021 (n = 537). Descriptive statistics and multivariable regression models were employed to understand different demographic, occupational, and immigration factors affecting migrant workers’ knowledge and awareness of treatment and immigration policies. Results Undocumented migrant workers had a longer length of residence in ROK and earned less compared to workers with work visa status. None of the undocumented migrant workers had access to health insurance since they were ineligible to enroll in the national health insurance scheme. In the early days of the pandemic, most undocumented migrant workers experienced a decrease in their average income. After adjusting for demographic differences and language proficiency, undocumented migrant workers (AOR: 0.41, 95% CI: 0.21, 0.78) were less likely to be aware of the policy allowing foreigners, including undocumented individuals, to access COVID-19 testing and treatment without the risk of deportation. Workers with a longer length of residence (AOR: 1.29, 95% CI: 1.09, 1.53) were more likely to be aware of this policy. Conclusion Undocumented migrant workers were often less informed about COVID-19 policies. While most of the survey respondents were knowledgeable about governmental policies regarding COVID-19 treatment and immigration, our results reveal multiple occupational and health insurance vulnerabilities of undocumented migrant workers living in ROK. More attention is needed to understand healthcare service barriers and how to provide adequate resources for this vulnerable population.